PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR IPAS MATERI KEANEKARAGAMAN BUDAYA DI KELAS V SDN 064976 MEDAN TEMBUNG - Tiarma Violita Tambunan; Yusra Nasution; Winara; Khairul Usman; Masta Marselina Sembiring (STKIP Subang, 2026)
This study aimed to determine the effect of the Contextual Teaching and Learning (CTL) model on students' learning outcomes in Science and Social Studies (IPAS) on the topic of cultural diversity among fifth-grade students at SD Negeri 064976 Medan Tembung. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 42 students divided into two groups: 21 students in the experimental class and 21 students in the control class. The research instrument was a multiple-choice learning outcomes test that had met validity and reliability requirements.Data were collected through pre-tests and post-tests. The results showed that the average pre-test score of the experimental class was 42.38, while the control class obtained 46.19. After the implementation of the CTL model, the average post-test score of the experimental class increased to 85.48, while the control class achieved 74.05. The hypothesis test using the Independent Sample t-Test indicated a significance value of 0.000 < 0.05. Therefore, H₀ was rejected and H1 was accepted. The findings indicate that the Contextual Teaching and Learning (CTL) model has a significant effect on students' learning outcomes in IPAS on the topic of cultural diversity at SD Negeri 064976 Medan Tembung.